Модифікація діамагнітних матеріалів за допомогою магнітних рідин - Safarik, I.; Prochazkova, J.; Baldikova, E.; Timko, M.; Kopcansky, P.; Rajnak, M.; Torma, N.; Pospiskova, K. (Publishing house "Academperiodika", 2020)
Magnetic fluids (ferrofluids) have found many important applications in various areas of biosciences, biotechnology, medicine, and environmental technology. In this review, we have summarized the relevant information dealing with a magnetic modification of diamagnetic materials using different types of ferrofluids. Special attention is focused on a magnetic modification of plant-derived biomaterials, microbial and microalgal cells, eukaryotic cells, biopolymers, inorganic materials, and organic polymers. Derivatization is usually caused by the presence of magnetic iron oxide nanoparticles within the pores of treated materials, on the materials surface or within the polymer gels. The obtained smart materials exhibit several types of responses to an external magnetic field, especially the possibility of the selective magnetic separation from difficult-to-handle environments by means of a magnetic separator. The ferrofluid-modified materials have been especially used as adsorbents, carriers, composite nanozymes or whole-cell biocatalysts.